Navigating Export Barriers in Emerging SMEs: Documentation, Tariff Challenges, and Adaptive Marketing Strategies in the Indonesian Export Sector - Evi Suwarni; Sudarmiatin Sudarmiatin; Heri Pratikto (Jurnal Manajemen Kewirausahaan dan Teknologi, 2026)
This study examines the export barriers encountered by emerging small and medium-sized enterprises (SMEs) in Indonesia, with a focus on export documentation challenges, tariff constraints, and the adaptive marketing strategies employed to sustain international market engagement. Employing a qualitative case study approach, this research investigates PT Albarka International Group, a nascent export-import company established in 2021 and headquartered in Malang, East Java, which specializes in the export of natural commodities including Bakhur-related materials (opercula shells, damar resin, agarwood), spices, and other Indonesian products to Middle East markets including Yemen, Saudi Arabia, UAE, Libya, Sudan, and Djibouti. Data were collected through in-depth interviews with key company personnel and supplemented by document analysis. Findings reveal three primary export barriers: (1) high shipping tariffs relative to regional competitors, frequently triggering order cancellations by importers; (2) complex and time-intensive export documentation requirements, particularly for regulated natural resource products subject to CITES compliance, fish quarantine certification (Health Certificate), and customs declaration (PEB); and (3) internal organizational constraints stemming from overlapping job roles. In response, PT Albarka has adopted adaptive strategies including Full Container Load (FCL) consolidation to reduce per-unit shipping costs, advance payment systems (TT in advance) to mitigate importer default risk, and collaborative consultation with customs and quarantine authorities. The study contributes to the SME internationalization literature by demonstrating how resource-constrained emerging exporters navigate institutional and logistical complexities in developing economy contexts, offering practical insights for SME practitioners and export policy stakeholders.